Synthesis of Some 2-Phenyl Imino Thiazolidine Condensed Pyrimidines - Singh, A.K.; Kumar, B.; Nag, A.K. (Asian Journal of Chemistry, 2010)
2-Phenyl imino thiazolidin-4-one was prepared by well known method and treated with different aromatic aldehydes to yield corresponding benzylidine derivatives (1-3). These benzylidine derivatives when treated separately with urea and thiourea resulted in their corresponding thiazolidino pyrimidines (4–9) (Scheme II).